Can Asian Communicators Think ? Asiacentricity as a Paradigm for Decolonizing the Asian Mind - Miike, Yoshitaka (Bodhi: An Interdisciplinary Journal, 2024)
Asiacentricity is the thought and practice of centering Asians as subjects and agents and Asian cultures as reflective resources in seeing and shaping the Asian world. This article contends that decolonizing the Asian mind is a key for the Asian future, and that the Asiacentric idea can play an important role in this decolonization process. The article divides the definition of Asiacentricity into three parts and then relates each part to the possible future developments of the sadharanikaran model of communication. The article especially sheds light on Asiacentricity as a decoloinal paradigm for intercultural equality and mutuality, which demands that we know our own culture, have the mindset of embracing the best of our culture, and learn how to talk about our culture in relation to another. The present article concludes that to theorize communication is to theorize humanity, while to theorize humanity is to theorize culture.